Exciplex Emitters: Prediction and Design of Efficient Exciplex Emitters for High‐Efficiency, Thermally Activated Delayed‐Fluorescence Organic Light‐Emitting Diodes (Adv. Mater. 14/2015). (April 2015) - Liu, Xiao‐Ke; Chen, Zhan; Zheng, Cai‐Jun; Liu, Chuan‐Lin; Lee, Chun‐Sing; Li, Fan; Ou, Xue‐Mei; Zhang, Xiao‐Hong
<x xml:space="preserve">Abstract</x> C.‐J. Zheng, C.‐S. Lee, X.‐H. Zhang, and co‐workers design three novel exciplex emitters by mixing three hole‐transporting arylamines with a high triplet energy bipolar host as shown on page 2378. The best exciplex‐based organic light‐emitting device shows strong thermally activated delayed fluorescence and realizes a high external quantum efficiency of 15.4%. In particular, strategies for predicting and designing efficient exciplex emitters are demonstrated to achieve efficient TADF exciplex emitters. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>